Symbolic Meaning of Dance with Masks People’s Life from Muaro/Jambi District - Pamela Mikaresti; Yesiska Mikaris; Citra Tamara (Proceeding International Conference on Malay Identity, 2020)
In the era of globalization,with rapid development and the number of entertainment are easily available, Dance with a mask that is always perfomedbypeopleliveiving inMuaro village Jambi, the subdistrict of MaroSebo, all in Muaro Jambi district, still exists and constantly developedin the life of itsfuns. Dance with a mask is able to maintain its existence even though in this era of globalization. In addition, the movements that concern with the Dance with masks, which always change, is not an obstacle for the village community of Jambi to continue preserving Dance with a mask and they routinely perform it.Basedonthephenomenonthatoccurs,todayistheright time forconducting a studyto determine and assessthemeaning of whatisreallycontained in thedance with a maskso thatit can bestillgrowing and developing in themodern era. The method used is the method of ethnography which is used to describe, record, analyze and interpret the Dance with a mask with the conditions of people inthe society who really and accurately support it.This research is a qualitative research, the research is done naturally, it is pure, in a normal situation that is not manipulated by circumstances and conditions. Hence, we get to know theDance with a mask symbolic meaning in people's lives acrosMuaro Jambi District. Key words: symbolic meaning, dance with a mask